If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=-6x+3(x+5)
We move all terms to the left:
12-(-6x+3(x+5))=0
We calculate terms in parentheses: -(-6x+3(x+5)), so:We get rid of parentheses
-6x+3(x+5)
We multiply parentheses
-6x+3x+15
We add all the numbers together, and all the variables
-3x+15
Back to the equation:
-(-3x+15)
3x-15+12=0
We add all the numbers together, and all the variables
3x-3=0
We move all terms containing x to the left, all other terms to the right
3x=3
x=3/3
x=1
| 2(u-6)+5u=9 | | 205=-y+48 | | -v+175=133 | | 268-w=170 | | y–4=-3 | | (3×18.50)+2x=104.50 | | 1/2•n=-3 | | 2Y=4x-30 | | x2+3x=-x+1 | | 5x-10+6=8x-28 | | 5x+2=68–x. | | 3(7–2n)=–3(5–n) | | 25-5w=4w | | 8(x-2+3x=61 | | 12.5=10.3+n | | x2−5x−20=−6 | | 10x-3=x=6 | | x/0.6=08/6.12 | | 3(x+2)+4(2x–1)=5(2x+5) | | 3n^2-22n-80=0 | | 10x-3x=6 | | -1/3+2m=1/5 | | -2x+9(-2x-8)=9+10(2x-8) | | -(2n-8)=-2n | | -y/7+9=-9 | | 2x-22=21 | | 3a-5a=a | | Y=6•7^x | | (x-1)(x-2)(x+3)=0 | | 5w-17=33 | | 31.5=4.5(3.25)-(20=5)x2 | | 180-17x=3x+(3^2*6x) |